Association between school environment and body mass index of primary school children in Terengganu - Rasyidah Ghazalli
Changes in dietary habits, sedentary lifestyle and environmental are known to be associated with the rising prevalence of obesity worldwide. Recently, the influence of school environment factor towards obesity-related dietary and physical activity behaviours become a great concern in obesity research. Therefore, the aim for this study was to investigate the association of school environment factors on children's body mass index (BMI) with the dietary intake and physical activity level as the confounding factors. The school environment was assessed using a set of validated Malay version "Whole-school Environmental Mapping" questionnaire, consists four main domains which are physical environment, economic environment, political environment and socio-cultural environment. It involved a face-to-face interview session with 32 teachers from 16 schools (8 rural and 8 urban) in Terengganu. In addition, a total of 400 school children aged 9 to I I years old of the selected schools were assessed for BMI according to WHO 2007 reference chart after measuring the weight and height, dietary intake using food frequency questionnaire (FFQ) and physical activity using physical activity questionnaire for children (PAQ-C). For the statistical analysis, multiple linear regression was used to examine the school environment factors associated with BMI of primary school children. The study found that overall school environment score for 16 schools in Terengganu was 63. I %. The political environment showed the highest score, 77.8%, whereas, the lowest score was the economic environment, 50.0%. The score for the physical and socio-cultural environment were 67.1% and 52.9%, respectively. In multiple linear regression analysis, seven criteria of school environment were found to be associated with BMI of school children when it was adjusted for calorie intake and physical activity level. The findings showed that 33.4% of the variation in BMI was explained by equation BMI (kg/m2) = 26.396 _ 3.063 (Health professional involvement) - 3.753 (Simple exercise available before class) + 1.120 (Encouragement of walking/riding bicycle to s hool) _ 2.999 (No high-calorie foods) - 1.75 I (Healthy foods and drinks at tuck shop) _ 2.735 (Policy for physical activity) + 1.498 (Training teacher as a role model). Awareness and enhancement of the school environment are needed in order to reduce the prevalence of overall childhood obesity.